Sympathetic nervous system controls resolution of inflammation via regulation of repulsive guidance molecule A - Andreas Körner (Nature Portfolio, 2019)
Diverse interactions between the nervous and immune systems have been shown, but specific mechanistic insights are still lacking. Here the authors show, using both mouse inflammation models and clinical correlation, that adrenergic nerve may ameliorate inflammation by inducing repulsive guidance molecule A signalling.